3′UTRs take a long shot in the brain. (20th September 2013) - Wang, Li; Yi, Rui
<x xml:space="preserve">Abstract</x> The fast advancing RNA‐seq technology has unveiled an unexpected diversity and expression specificity of 3′ untranslated regions (3′UTRs) of mRNAs. In particular, neural mRNAs seem to express significantly longer 3′UTRs, some of which are over 10 kb in length. The extensive elongation of 3′UTRs in neural tissues provides intriguing possibilities for cell type‐specific regulations that are governed by miRNAs, RNA‐binding proteins and ribonucleoprotein aggregates. In this article, we review recent progress in the characterization of mRNA 3′UTRs and discuss their implications in the understanding of 3′UTR‐mediated gene regulation.